Samuel Johnson, the Ossian fraud, and the Celtic revival in Great Britain and Ireland - Curley, Thomas M. (Cambridge University Press, 2009)
James Macpherson's famous hoax, publishing his own poems as the writings of the ancient Scots bard Ossian in the 1760s, remains fascinating to scholars as the most successful literary fraud in history. This study presents the fullest investigation of his deception to date, by looking at the controversy from the point of view of Samuel Johnson. Johnson's dispute with Macpherson was an argument with wide implications not only for literature, but for the emerging national identities of the British nations during the Celtic revival. Thomas M. Curley offers a wealth of genuinely new information, detailing as never before Johnson's involvement in the Ossian controversy, his insistence on truth-telling, and his interaction with others in the debate. The appendix reproduces a rare pamphlet against Ossian written with the assistance of Johnson himself. This book will be an important addition to knowledge about both the Ossian controversy and Samuel Johnson.